Climate and Biodiversity Nexus: Strategies for Sustainable Forestry in Europe - Anu Vettathuparambil Velayudhan; Carlo Jaeger (Forest and Nature, 2025)
Balancing climate change mitigation with biodiversity conservation remains a pivotal challenge for sustainable forest management in Europe. This study investigates the nexus between carbon sequestration and biodiversity across European forest regions from 1990 to 2020, integrating data on forest biomass, carbon stock, and biodiversity indicators using statistical modeling in R. Results show a steady increase in forest area and carbon stocks, particularly in Central-East and Central-West Europe, driven by afforestation and adaptive forest policies. However, biodiversity responses vary by region and the intensity of management. Forests under low-intensity or semi-natural management, particularly mixed-species stands, exhibit positive correlations between carbon stock and biodiversity metrics, such as species richness and the Shannon index. In contrast, intensively managed monocultures—such as Eucalyptus plantations in Southwestern Europe—exhibit rapid carbon gains but reduced ecological resilience, characterized by low evenness and structural diversity. Generalized additive models (GAMs) reveal non-linear, species- and region-specific dynamics in the carbon-biodiversity relationship, emphasizing the importance of ecological context. These findings highlight critical trade-offs and synergies in forest management, calling for integrated policies that consider forest structure, species composition, and long-term ecosystem resilience. The study recommends regionally differentiated strategies, stronger biodiversity monitoring, and enhanced policy coherence to align with the EU Green Deal and Forest Strategy 2030, advancing Europe’s path toward climate-smart, biodiversity-rich forestry.